Educational inclusion of students with disabilities at the Central University of Ecuador - Moreno-Pramatárova , Mila (2022)
Introduction: Educational inclusion in public and private higher education is a problem that has been addressed in various ways by different Ecuadorian higher education institutions. The Central University of Ecuador is a public institution where approximately 40,000 students study, is committed to implementing inclusive cultures, policies and practices, which analyzes the barriers and opportunities for access to quality education and on equal terms. Aim. Identify the personal characteristics of students with disabilities, the contextual factors of the Central University of Ecuador and their relationship with the level of inclusion. Material and methods. Descriptive, correlational, observational study, which investigated 108 students from the Central University of Ecuador who present at least one disability, and who answered the inclusion survey online. Statistic analysis. SPSS 22.0 was used, for the univariate analysis applied descriptive statistics supported by measures of proportion while x2 squared and Spearman tests were used for the bivariate analysis. Results. 54% of those investigated register a low level of educational inclusion, 22.52% present limitations to move around, 17.59% to learn/study and 14.81% for personal interactions. 35% require help from classmates and family, university services and technical aids to carry out several of their academic activities and access the university physical environment with severe and moderate limitations to carry out their activities are 1.4 to 1.8 times more likely to have a low level of inclusion than those with mild limitations. This pattern is repeated with other personal and contextual variables and reflects the association between personal-contextual factors and educational inclusion. Conclusions. Inclusion is a systemic process in which bio-psycho-social variables intervene and interact concurrently. The conditions to create the educational inclusion of students with disabilities in the Central University of Ecuador must be supported by a paradigm shift, and oriented towards the implementation of educational inclusion policies and processes, which incorporate the needs expressed by those investigated in this study.